Beneficial Effects of Norepinephrine Alone on Cardiovascular Function and Tissue Oxygenation in a Pig Model of Cardiogenic Shock. Issue 2 (August 2016) - Beurton, Alexandra; Ducrocq, Nicolas; Auchet, Thomas; Joineau-Groubatch, Frédérique; Falanga, Aude; Kimmoun, Antoine; Girerd, Nicolas; Fay, Renaud; Vanhuyse, Fabrice; Tran, Nguyen; Levy, Bruno
Abstract : ABSTRACT: Introduction: The present study was developed to investigate the effects of norepinephrine alone on hemodynamics and intrinsic cardiac function in a pig model of cardiogenic shock mimicking the clinical setting. Methods: Cardiogenic shock was induced by 1-h ligation of the left anterior descending (LAD) artery followed by reperfusion. Pigs were monitored with a Swan-Ganz catheter, a transpulmonary thermodilution catheter, and a conductance catheter placed in the left ventricle for pressure-loop measurements. Measurements were performed before LAD occlusion, 1 h after LAD occlusion, and 4 h after myocardial reperfusion. Results: Myocardial infarction and reperfusion was followed by cardiogenic shock characterized by a significant increase in heart rate and significant decreases in mean arterial pressure (MAP), mixed venous oxygen saturation (SVO2 ), left ventricular end-diastolic pressure (LVEDP), prerecruitable stroke work (PRSW), and cardiac power index (CPI). Lactate levels were significantly increased. The systemic vascular resistance index (SVRI) and global end-diastolic volume index (GEDVI) remained unchanged. When compared with the control group (n = 6), norepinephrine infusion (n = 6) was associated with no changes in heart rate, a significant increase in MAP, SVO2, left ventricular ejection fraction, pressure development during isovolumic contraction, SVRI, and CPI and a decrease in lactate level. Cardiac index tended to increase ( P  = 0.059), whereas PRSW did not change in the norepinephrine group. LVEDP and GEDVI remained unchanged. Conclusions: Norepinephrine alone is able to improve hemodynamics, cardiac function, and tissue oxygenation in a pig model of ischemic cardiogenic shock. Abstract : Supplemental Digital Content is available in the text